2017
DOI: 10.1007/s00414-017-1659-6
|View full text |Cite|
|
Sign up to set email alerts
|

Sex estimation of infants through geometric morphometric analysis of the ilium

Abstract: In archeology or forensics, the analysis of the ilia is often used to determine the age and sex of unknown individuals. However, sex determination using the skeletal remains of individuals who did not develop secondary sexual characteristics remains controversial. Accurately estimating the sex of subadults is hampered by a small number of studies based on identified skeletal collections of juvenile individuals. Here, we analyzed the sexual dimorphism of the subadult ilia using geometric morphometric techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The morphological approach proposed by Luna and co‐workers seems to be replicable in populations from different geographical areas, even though it would be useful to test the procedure on other identified samples outside the Mediterranean area. As already suggested in previous studies, in order to improve the accuracy of subadult sex estimation, it will be useful to incorporate the results of the morphology of the auricular surface into a multifactorial approach, combining several pelvic variables with other osseous and tooth features (Mittler & Sheridan, 1992; Schutkowski, 1993; Sutter, 2003; Cardoso, 2008; Cardoso & Saunders, 2008; Zadzinska et al, 2008; Wilson et al, 2008; Irurita & Alemán, 2016; Estévez et al, 2017; Stull et al, 2017) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphological approach proposed by Luna and co‐workers seems to be replicable in populations from different geographical areas, even though it would be useful to test the procedure on other identified samples outside the Mediterranean area. As already suggested in previous studies, in order to improve the accuracy of subadult sex estimation, it will be useful to incorporate the results of the morphology of the auricular surface into a multifactorial approach, combining several pelvic variables with other osseous and tooth features (Mittler & Sheridan, 1992; Schutkowski, 1993; Sutter, 2003; Cardoso, 2008; Cardoso & Saunders, 2008; Zadzinska et al, 2008; Wilson et al, 2008; Irurita & Alemán, 2016; Estévez et al, 2017; Stull et al, 2017) .…”
Section: Discussionmentioning
confidence: 99%
“…Various features were analyzed, such as the greater sciatic notch (Boucher, 1957; Weaver, 1980; Schutkowski, 1993; Holcomb & Konigsberg, 1995; Sutter, 2003; Vlak et al, 2008, Wilson et al, 2008; Wilson, Cardoso, & Humphrey, 2011; Irurita & Alemán, 2016), the subpubic concavity (Klales & Burns, 2017), the auricular surface elevation (Hunt, 1990; Mittler & Sheridan, 1992; Sutter, 2003; Weaver, 1980), the arch criterion (Schutkowski, 1993; Sutter, 2003; Cardoso & Saunders, 2008; Irurita & Alemán, 2016), the curvature of the iliac crest (Schutkowski, 1993; Sutter, 2003, Wilson et al, 2008, 2011; Irurita & Alemán, 2016) and the auricular surface morphology (Luna et al, 2017; Wilson et al, 2008, 2011). Recently, a successful approach has been carried out through geometric morphometrics analysis of the ilium (Wilson et al, 2008; Wilson et al, 2011; Estévez, López‐Lázaro, López‐Morago, Alemán, & Botella, 2017), while the application of advanced morphometric techniques in order to investigate the presence of sexual dimorphism of the immature pubis and ischium was less successful (Campo et al, 2018). Frequently, these proposed methods achieved very high sexing accuracies in the original study, while other validation studies obtained worse results.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current results are consistent with those obtained by Holcomb [19], in which she found significant effects of sex on overall ilia outlines but not localized GSN variables. Even those studies that previously reported significant sex differences in the subadult GSN, ultimately had cross‐validated correct classification results in the 50th or 60th percentiles (e.g., [7,9]).…”
Section: Discussionmentioning
confidence: 99%
“…Access to subadult skeletal samples is highly limited and many of these studies are based on skeletal collections from the early 1900s or before (e.g., [6,7,9,15,16,19,21]). Studies using modern samples suffer from small sample sizes or limited ranges of subadult ages (e.g., [17,20]); appropriate sample sizes for all chronological ages of interest are needed to accurately capture age-related changes in subadult traits [22].…”
Section: Introductionmentioning
confidence: 99%
“…Estimation of sex in adults was based on established morphoscopic criteria, principally, in the skull and ilium (Buikstra and Ubelaker 1994). In subadult individuals, estimation of sex utilized the methodology employed by Estévez et al (2017), Hernández and Peña (2010), Loth and Henneberg (2001), Schutkowski (1987, 1993), and Sutter (2003) based on several morphological features: amplitude of the angle of the greater sciatic notch, curvature of the ilium, and depth of the greater sciatic notch, as well as features of the mandible such as the protrusion of the chin region and shape of the anterior dental arcade, along with the size of the mastoid process in the skull. Sex determination for children over four years of age was evaluated using two variables: the eversion of the gonion and the shape of the supra–orbital margin.…”
Section: Laboratory Methodsmentioning
confidence: 99%